2020
DOI: 10.1002/admi.202000484
|View full text |Cite
|
Sign up to set email alerts
|

3D BaTiO3 Flower Based Polymer Composites Exhibiting Excellent Piezoelectric Energy Harvesting Properties

Abstract: Piezoelectric nanogenerators (PENGs) with good flexibility and high outputs have promising applications in harvesting mechanical energy and powering electronics. In this study, a synthesis of hierarchical BaTiO3 flowers (BTFs) and their filling into the polydimethylsiloxane (PDMS) matrix to obtain composites with excellent energy harvesting properties is reported. The BTF‐based PENG possesses a voltage of 260 V, a current of 50 µA, and a power of 1728 µW under a compression of 50 N at 3.5 Hz, which output powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…The piezoelectricity of the composites is enhanced by increasing the addition of inorganic BNdT NPs, which results in the increase in output voltage. On the other hand, further increasing the inorganic fillers will deteriorate the flexibility of the composites and the efficiency of strain transfer, leading to the decrease in the generated voltage [27]. The piezoelectric output of the BNdT NPs/PDMS f-PEHs were measured on a purpose-built platform in the repetitive tapping mode.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The piezoelectricity of the composites is enhanced by increasing the addition of inorganic BNdT NPs, which results in the increase in output voltage. On the other hand, further increasing the inorganic fillers will deteriorate the flexibility of the composites and the efficiency of strain transfer, leading to the decrease in the generated voltage [27]. The piezoelectric output of the BNdT NPs/PDMS f-PEHs were measured on a purpose-built platform in the repetitive tapping mode.…”
Section: Resultsmentioning
confidence: 99%
“…The flexible PEHs (f-PEHs) fabricated with composites of inorganic piezoelectric nanostructures dispersed in polymer matrix exhibit high electrical output and high flexibility [16][17][18]. Various piezoelectric nanostructures, such as nanoparticles [19][20][21][22], nanowires [23][24][25][26] nanoflowers [27], nanofibers [28], and nanocubes [29] etc., have been used as fillers to disperse into polydimethylsiloxane (PDMS) [30] or polyvinylidene fluoride (PVDF) polymers [31], etc. It has also been found that the morphology of the fillers has an important influence on the output performance of the f-PEHs [22,29,[32][33][34], because the high dimensional piezoelectric fillers enhance the continuity of fillers and also the transferring efficiency of stress from the matrix to the active inclusions [27], which thus improves the output performance of the PEHs [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…reported the polydimethylsiloxane (PDMS) composites filled with hierarchical BaTiO 3 flowers (BTFs). [ 37 ] The BTF‐based PENG obtained a V OC of 260 V, an I SC of 50 µA, and a power of 1728 µW, which showed significantly enhanced energy scavenging properties compared with that of polymer composites filled with BT nanoparticles (NPs). They analyzed the simulated electric potential and stress under 50 N pressure through finite element analysis on PENGs.…”
Section: Materials Fabrication and Performance Enhancementmentioning
confidence: 99%